Synthesis of reactive MgO from reject brine - Dong, Haoliang (2018)
Portland cement (PC) is the most common binder used in concrete and construction materials. The production of PC is estimated to be at 3 billion tonnes yearly at a global scale, being responsible for 5-7% of anthropogenic CO2 emissions worldwide. Reactive magnesia (MgO) cement has received attention as an alternative binder due to the lower calcination temperatures (~700 °C) used during its production, its ability to store CO2 permanently while gaining strength, and complete recyclability at the end of use. However, the sustainable production of reactive MgO remains a challenge. Reject brine, which is a concentrated by-product with a high salt concentration obtained from treating brackish water or seawater in desalination plants, provides an ideal alternative to recover reactive MgO due to the high concentrations of Mg. This research focuses on identifying different routes to synthesize and characterize the precursors, i.e. Mg(OH)2, hydrated magnesium carbonates (HMCs) and MgC2O4•2H2O from reject brine, and to investigate the potential of the production of reactive MgO with high purity and reactivity. The relationships between the calcination conditions, e.g. calcination temperatures and durations, and reactivities of MgO have been explored. The phase change of HMCs and the carbon storage efficiency via the injection of CO2 into Mg(OH)2 slurries generated from reject brine are comprehensively studied. Finally the economic feasibility, energy consumption and carbon footprint of the production of reactive MgO from reject brine via different routes have been calculated and presented by means of life cycle assessment (LCA)